2016
DOI: 10.1103/physrevx.6.041058
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Weak Collapse in a Bose-Einstein Condensate

Abstract: We study the collapse of an attractive atomic Bose-Einstein condensate prepared in the uniform potential of an optical-box trap. We characterize the critical point for collapse and the collapse dynamics, observing universal behavior in agreement with theoretical expectations. Most importantly, we observe a clear experimental signature of the counterintuitive weak collapse, namely, that making the system more unstable can result in a smaller particle loss. We experimentally determine the scaling laws that gover… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 61 publications
(76 reference statements)
0
36
1
Order By: Relevance
“…Note that, when we encounter a collapse, we observe the disappearance of all condensed atoms. This is in contrast with recent experiments done in 3D Bose-gases trapped in a box potential [44].…”
contrasting
confidence: 94%
“…Note that, when we encounter a collapse, we observe the disappearance of all condensed atoms. This is in contrast with recent experiments done in 3D Bose-gases trapped in a box potential [44].…”
contrasting
confidence: 94%
“…As is well known, 3D self-attractive BECs are unstable against collapse [15][16][17][18][19] whenever the coupling strength exceeds a certain critical value (however, see [20]). The collapse has been observed and extensively studied experimentally too [21][22][23][24][25][26][27]. On the theoretical side, a study of direct relevance to the present work was reported in Ref.…”
Section: Introductionmentioning
confidence: 66%
“…Under this condition we can get λ c = 0 when ω r − χ ″ = κ and δ = 0 or when ω r − χ ″ = 2 κ and δ = 1. A realistic estimation of the present model parameters can be obtained from recent experiments 2 , 45 48 . From the experiments in refs 2 and 45 , we find the parameters ω ~ MHz, ω r ~ KHz, { l x , l y , l z } ~ {3.2, 16.6, 3.3} μ m, and N ~ 10 5 .…”
Section: Resultsmentioning
confidence: 99%
“…This condition can be obeyed for the BEC with attractive interactions between atoms. According to refs 2 , 45 48 , stable BECs with the negative s -wave scattering lengths can be obtained for Rubidium atoms and Potassium atoms. The stability of the BEC with the attractive interactions between atoms is characterized by the stability parameter C = N | a |/ l 0 with l 0 being mean harmonic oscillator length 46 .…”
Section: Resultsmentioning
confidence: 99%